The Rivalry Effect: The Potential to Foster (Lapsed) Donor Giving - Katherine R. N. Reifurth; Kelly M. Evans; Jeffrey D. James; Yong Jae Ko (Journal of Applied Sports Management, 2019)
Prior sport rivalry researchers have failed to examine the effects of rivalry utilizing a multidimensional approach to team identification as well as the effects of rivalries in relation to the behavioral outcomes of lapsed donors. The authors worked with the official booster club of a large public university to create three distinct email campaigns targeting lapsed donors to test the effects of framing donation requests with rivalry-themed communications. The results of this study highlight the variations in these distinct identification dimensions due to the presence of a rivalry as well as the behavioral effects a rivalry has on these lapsed donors.
Keywords: Rivalry; team identification; behavioral outcomes; lapsed donors